Replantation and reconstructive microvascular surgery. Part I. - O'Brien, B. M. (Royal College of Surgeons of England, 1976)
Although the operating microscope was introduced more than 50 years ago, its use was at first confined to otolaryngology and, later, to ophthalmology. More recently its use in the development of microvascular techniques has led to spectacular advances in the field of replantation and reconstructive surgery. The organization of microsurgical research at St Vincent's Hospital, Melbourne, is briefly described and clinical experience at this hospital over the past 10 years is reviewed. This includes 86 cases of digital replantation, with survival rates of 58% for complete and 82% for incomplete amputation, and 14 cases of major replantation (amputations proximal to the metacarpophalangeal joints) with a survival rate of 71%. In the second part of the lecture the use of microsurgery for composite tissue transfer and one-stage toe-to-hand transfer is discussed and experimental and clinical experience in microlymphatic surgery described.